París se hace poema - De Diego, Rosa (Anales de Filología Francesa, 2009)
This article analyses the relations between poetry and modern city, especially Paris, since the industrial revolution which take place in the XIX century. After take a look at the urban transformations made in that period, its studied how is this city imagined, the capital of modernity for some poets like Baudelaire, Verhaeren or Jules Romains.